Analisis Kemampuan Literasi Sains Peserta didik SMP di Kota Cirebon - Fanni Zulaiha; Dewi Kusuma (Department of Physics Education, Universitas Mataram, 2021)
Scientific literacy was chosen as the main goal of science education. As the main goal, scientific literacy in science education is a picture of success in science education carried out by each country. In Indonesia, policies have been taken to support this goal although it is not clearly explained. To find out the success of science learning in the city of Cirebon, the researchers felt the need to analyze the scientific literacy skills of students in the city of Cirebon before providing concrete solutions to the problems faced. This study aims to provide an overview of the scientific literacy skills of junior high school students in Cirebon City. The research design used is quantitative research that uses descriptive (descriptive-quantitative) methods, namely research whose descriptions use size, number or frequency. The study was conducted on 7th grade students at the Cirebon City State Junior High School. The sample used was purposive sampling. The sample selected was State Junior High School with A and B accreditation. The scientific literacy ability in this study was viewed from the aspect of competence, knowledge and context. Based on the results of data processing, as many as 72.13% of seventh grade junior high school students in the city of Cirebon have scientific literacy skills in a very low category. This scientific literacy becomes a reference in applying the ability and quality of science learning in Cirebon City.